In vitro activity of photoactivated disinfection using a diode laser in infected root canals. (November 2014) - Schiffner, Ulrich; Cachovan, Georg; Bastian, Jochen; Sculean, Anton; Eick, Sigrun
Abstract Objective. To investigate the lethal activity of photoactivated disinfection (PAD) on Enterococcus faecalis (ATCC 29212) and mixed populations of aerobic or anaerobic bacteria in infected root canals using a diode laser after the application of a photosensitizer (PS). Materials and methods. First, the bactericidal activity of a low power diode laser (200 mW) against E. faecalis ATCC 29212 pre-treated with a PS (toluidine blue) for 2 min were examined after different irradiation times (30 s, 60 s and 90 s). The bactericidal activity in the presence of human serum or human serum albumin (HSA) was also examined. Second, root canals were infected with E. faecalis or with mixed aerobic or anaerobic microbial populations for 3 days and then irrigated with 1.5% sodium hypochlorite and exposed to PAD for 60 s. Results. Photosensitization followed by laser irradiation for 60 s was sufficient to kill E. faecalis. Bacteria suspended in human serum (25% v/v) were totally eradicated after 30 s of irradiation. The addition of HSA (25 mg/ml or 50 mg/ml) to bacterial suspensions increased the antimicrobial efficacy of PAD after an irradiation time of 30 s, but no longer. The bactericidal effect of sodium hypochlorite was only enhanced by PAD during the early stages of treatment. PAD did not enhance the activity of sodium hypochlorite against a mixture of anaerobic bacteria. Conclusions. The bactericidal activity of PAD appears to be enhanced by serum proteins in vitro, but is limited to bacteria present within the root canal.